Identification of French Guiana sand flies using MALDI-TOF mass spectrometry with a new mass spectra library - Chavy, Agathe (Public Library of Science, 2019)
Phlebotomine sand flies are insects that are highly relevant in medicine, particularly as the sole proven vectors of leishmaniasis. Accurate identification of sand fly species is an essential prerequisite for eco-epidemiological studies aiming to better understand the disease. Traditional morphological identification is painstaking and time-consuming, and molecular methods for extensive screening remain expensive. Recent studies have shown that matrix-assisted laser desorption and ionization time-of-flight mass spectrometry (MALDI-TOF MS) is a promising tool for rapid and cost-effective identification of arthropod vectors, including sand flies. The aim of this study was to validate the use of MALDI-TOF MS for the identification of Northern Amazonian sand flies. We constituted a MALDI-TOF MS reference database comprising 29 species of sand flies that were field-collected in French Guiana, which are expected to cover many of the more common species of the Northern Amazonian region, including known vectors of leishmaniasis. Carrying out a blind test, all the sand flies tested (n = 157) with a log (score) threshold greater than 1.7 were correctly identified at the species level. We confirmed that MALDI-TOF MS protein profiling is a useful tool for the study of sand flies, including neotropical species, known for their great diversity. An application that includes the spectra generated here will be available to the scientific community in the near future via an online platform.